Colombia's response to healthcare crisis. (23rd February 2012) - Bernal, Oscar; Forero, Juan Camilo; Forde, Ian
Abstract : In 2009 Colombia declared a state of emergency in its healthcare system. Oscar Bernal, Juan Camilo Forero, and Ian Forde describe the origins of the crisis and explore the extent to which the reforms that followed are likely secure better healthcare for the population